IMPLEMENTASI HAK ASASI MANUSIA TERHADAP REHABILITASI TAHANAN DI LAPAS NARKOTIKA SAMARINDA - INTEN SETIOWATI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTNumber of drug users in Indonesia. Currently almost 5 million Indonesians are drug addicts, it makes the entry of drugs illegally into Indonesia as if never stopped, either through land border, sea or air, should the addicts be noticed by their respective families and then submitted for Immediate rehabilitation of drug users, if not rehabilitated it will never recover and escape from the influence of the drug. Punishment is not optimal for drug dealers. The punishment should be given to the perpetrators of drugs is maximum punishment in the hope that the person is sorry for his actions and carried out coaching in order to change his life with the skills given as living capital when it is free. Human rights protection should not be the burden of the state, but it is the way the government carries out its mandate as the highest authority organization. The victim's problem in Law Number 35 Year 2009 is because it uses various terms namely "addict", "patient", "abuser" "Victims of abusers". The Narcotics Correctional Institution of Samarinda City categorizes narcotic drug into several levels of narcotics users. Correctional institutions are expected to run a penitentiary system so that convicted narcotics (or known as prisoners / WBP) are aware of mistakes, improve themselves, do not repeat So that criminal acts, can be accepted back by the community environment, Can actively play a role in development, and can live as a reasonable life a good and responsible citizen, and not a recidivistKeywords  :  Human Rights, Coaching Prisoners, Narcotics